2017
DOI: 10.1158/1078-0432.ccr-17-0913
|View full text |Cite
|
Sign up to set email alerts
|

Numb−/low Enriches a Castration-Resistant Prostate Cancer Cell Subpopulation Associated with Enhanced Notch and Hedgehog Signaling

Abstract: To elucidate the role and molecular mechanism of Numb in prostate cancer and the functional contribution of Numb prostate cancer cells in castration resistance. The expression of Numb was assessed using multiple datasets and prostate cancer tissues from both humans and mice. The biological effects of the overexpression and knockdown of Numb in human prostate cancer cell lines were investigated and In addition, we developed a reliable approach to distinguish between prostate cancer cell populations with a high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Interestingly, asymmetric divisions in which PSA −/low cells generate a PSA + daughter also showed differential segregation of Numb (Qin et al 2012), a putative cell fate determinant that has been implicated in asymmetric divisions in multiple systems (Bajaj et al 2015). Consistent with this finding, Numb −/low cells isolated from a range of prostate cancer cell lines had increased tumor initiation relative to Numb + cells, and displayed greater castration resistance (Guo et al 2017).…”
Section: Jiao Et Al 2012supporting
confidence: 52%
“…Interestingly, asymmetric divisions in which PSA −/low cells generate a PSA + daughter also showed differential segregation of Numb (Qin et al 2012), a putative cell fate determinant that has been implicated in asymmetric divisions in multiple systems (Bajaj et al 2015). Consistent with this finding, Numb −/low cells isolated from a range of prostate cancer cell lines had increased tumor initiation relative to Numb + cells, and displayed greater castration resistance (Guo et al 2017).…”
Section: Jiao Et Al 2012supporting
confidence: 52%
“…For advanced and metastatic prostate cancer, the therapeutic focus has largely revolved around androgen deprivation therapy (ADT) which usually achieves short-term effectiveness but ultimately induces drug resistance and metastasis 10,31 . Increasing evidence has indicated that ADT induces the enrichment of PCSCs subpopulation, which are resistant to traditional killing strategies and drive subsequent metastasis [32][33][34] . Therefore, eliminating PCSCs is crucial for improving the clinical outcomes of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, approximately 50 chemokines have been identified 46 and several TAMs-derived chemokines have been reported to be associated with cancer progression and metastasis. For example, it has been reported that TAMs could promote prostate cancer migration through activation of the CCL22-CCR4 axis 32 . TAMs released CCL18 to further promote the aggressive phenotype of breast phyllodes tumors by enhancing and maintaining the myofibroblast differentiation and invasion in vitro and in vivo 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT), when applied to advanced and recurrent prostate cancers, achieves short-term effectiveness, but ultimately induces drug resistance, leading to increased cancer-related deaths (6,7). Increasing evidence has indicated that ADT induces reprogramming of prostate cancer and enriches a subpopulation of cells with CSC properties, which are resistant to ADT and drive prostate cancer progression (8,9). Therefore, eliminating CSCs may be crucial for achieving a good response of prostate cancer to ADT.…”
Section: Introductionmentioning
confidence: 99%